2017
DOI: 10.1155/2017/4634235
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Solitary Fibrous Tumor: A “Patternless” Tumor

Abstract: Introduction Solitary fibrous tumor is a rare type of mesenchymal, spindle-cell tumor reported mostly in the pleura. Retroperitoneal occurrence is rare and histopathological diagnosis is challenging. Case Presentation A 55-year-old woman with nonspecific abdominal pain was found to have a retroperitoneal/pelvic mass adjacent to the upper rectum. The patient underwent surgical resection in clear margins of this pelvic tumor, entering the total mesenteric excision surgical plane. Final histopathology revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…[8] In the literature, there is no specific laboratory test available for the diagnosis of SFT-HMP. Myoteri et al [4] suggested using glucose levels due to the fact that 10% of the patients have hypoglycemia due to increased production of Insulin like Growth Factor 2. Differentiation between SFT-HMP and other solid tumors is also not possible using radiological studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] In the literature, there is no specific laboratory test available for the diagnosis of SFT-HMP. Myoteri et al [4] suggested using glucose levels due to the fact that 10% of the patients have hypoglycemia due to increased production of Insulin like Growth Factor 2. Differentiation between SFT-HMP and other solid tumors is also not possible using radiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Deep muscles of proximal extremity, head, neck and retroperitoneum are common locations for extrapleural SFT. [4] Penile SFT-HMP was mentioned in the literature in two separate case reports which were published in 2015 and 2017. [5,6] We present the first case of SFT-HMP which was localized on corpus cavernosum of the penis.…”
Section: Introductionmentioning
confidence: 99%
“…The differential diagnosis of primary retroperitoneal masses is given in Table 1 7 . As the case described above, SFTs in the retroperitoneum are rarely found and less than 100 cases have been described so far 2 . The main feature of SFTs is the large size they can reach as they do not have any specific symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, it has been reported in many extrapleural sites but is found to be exceedingly rare. Most of them are reported to arise from the pleura, and only 30% are of extrapleural origins 2 . Less than a hundred cases of primary retroperitoneal solitary fibrous tumors have been described till now.…”
Section: Introductionmentioning
confidence: 99%
“…Leiomyoma may show similar morphology, but its vessels are usually capillaries, along with a few arterioles and small arteries, in contrast to the thick-walled vessels of the ALM. Solitary fibrous tumor can occur at unusual sites 13-18 and rarely may present as a retroperitoneal/pelvic mass 19 20 . Unlike ALM, it shows a hemangiopericytomatous vasculature, with a typical branching configuration and perivascular hyalinization.…”
Section: Discussionmentioning
confidence: 99%